REKONSTRUKSI PERLINDUNGAN HUKUM KONSUMEN ATAS DARK PATTERNS LAYANAN BERLANGGANAN DIGITAL DI INDONESIA - Monaliza Kalalembang; Yimmy Octavian Yapri; Riris Siregar; Hendrico Dolok; Paltiada Saragi (Honeste Vivere, 2026)
The digital economy has transformed consumer access to goods and services via electronic platforms. While enhancing convenience, digitalization introduces manipulative business practices like "dark patterns"—interface designs intentionally crafted to influence user behavior for commercial gain. In digital subscription services, these manifest as auto-renewals, unnotified post-trial charges, pre-selected paid add-ons, and deliberately complex cancellation processes. Using a normative juridical method with statutory, conceptual, and comparative approaches, this study examines dark pattern characteristics, evaluates the adequacy of Indonesian consumer protection law, and proposes a legal reconstruction model. Findings reveal that while Indonesian law provides a foundational framework through accurate information rights, good faith obligations, and standard clause regulations, it lacks explicit provisions targeting manipulative interface design as an unfair commercial practice. Consequently, this study introduces design justice as a new paradigm for digital consumer protection, subjecting digital interfaces directly to legal oversight.